#MeToo: avoiding the risk of sexual harassment claims. (2nd December 2020) - Bernstein, Adam
Abstract : Issues relating to sexual harassment in the workplace have not disappeared. Adam Bernstein examines the rise of the#MeToo movement, its impact and what businesses must do to keep their employees safe.